Rio de Janeiro as a Park of Ruins: Digging through Images in a Site-Specific Poetry Book - Klinger, Diana; Ximenes, Vinícius (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2021)
This text proposes a reading of Parque das ruínas (Ruins Park, 2018), a poetry book by Marília Garcia, which places words and images in a dialogue in order to question ways of seeing through constant changes of spatial and temporal scales. Mediated by optical devices, it exposes a body of perception as crossed by “practices, techniques, institutions, and procedures of subjectivation” (Crary, 2012). Our aim here is also a re-assembling of the book’s images in their relation to Rio de Janeiro’s history grounded in slavery and their related struggles regarding memory. By referring to the archaeological strata of Rio de Janeiro’s formation, moving through the “ruins” of its modern institutions such as the museum and the university discussed in Garcia’s book, we suggest an underlying sense that ties the poem to the present dynamics of extractive capitalism.